(untitled) (Itinera, 2025)
The paper addresses the development of ecological art or Eco Art movements since the inception of the new millennium, focussing on the re-mediation of artistic practices towards sustainable futures and the emerging remedies in the quest for biodiversity consciousness. Starting with an analysis of engagement as a peculiar legacy of the 20th century Avant-Gardes, the paper discusses the shift in the 21st century with regard to the environmental awareness of artists engaged in sustainability. The paper argues that practitioners and practices have evolved in a twofold direction: on the one side towards a manifest way of positioning themselves in relation to sustainability issues, while on the other side exploring a set of postmodernist devices as societal remedies in the frame of biodiversity topics.